Satellite observations of chlorophyll, phytoplankton biomass, and Ekman pumping in nonlinear mesoscale eddies. Issue 12 (2nd December 2013) - Gaube, P.; Chelton, D. B.; Strutton, P. G.; Behrenfeld, M. J.
Abstract : [1] Nonlinear mesoscale eddies can influence biogeochemical cycles in the upper ocean through vertical and horizontal advection of nutrients and marine organisms. The relative importance of these two processes depends on the polarity of an eddy (cyclones versus anticyclones) and the initial biological conditions of the fluid trapped in the core of the eddy at the time of formation. Eddies originating in the eastern South Indian Ocean are unique in that anticyclones, typically associated with downwelling, contain elevated levels of chlorophyll‐a, enhanced primary production and phytoplankton communities generally associated with nutrient‐replete environments. From analysis of 9 years of concurrent satellite measurements of sea surface height, chlorophyll, phytoplankton carbon, and surface stress, we present observations that suggest eddy‐induced Ekman upwelling as a mechanism that is at least partly responsible for sustaining positive phytoplankton anomalies in anticyclones of the South Indian Ocean. The biological response to this eddy‐induced Ekman upwelling is evident only during the Austral winter. During the Austral summer, the biological response to eddy‐induced Ekman pumping occurs deep in the euphotic zone, beyond the reach of satellite observations of ocean color. Key Points: Elevated CHL is observed in anticyclones of the South Indian Ocean during winter Eddy‐induced Ekman pumping can sustain elevated CHL in anticyclones CHL anomalies in eddy are likely too deep to be observed by satellites in summer